2011
DOI: 10.1016/j.jas.2011.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Upper Palaeolithic hunter-gatherer subsistence in Mediterranean coastal environments: an isotopic study of the diets of the earliest directly-dated humans from Sicily

Abstract: a b s t r a c tThe subsistence of hunter-gatherers in the Mediterranean Basin has been the object of few studies, which have not fully clarified the role of aquatic resources in their diets. Here we present the results of AMS radiocarbon dating and of isotope analyses on the earliest directly-dated human remains from Sicily, the largest island in the Mediterranean Sea. The radiocarbon determinations show that the Upper Palaeolithic (Epigravettian) humans from Grotta di San Teodoro (15 232e14 126 cal. BP) and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 26 publications
(26 reference statements)
2
39
0
Order By: Relevance
“…This complex dates to around the Last Glacial Maximum and includes species such as Equus hydruntinus (European ass) that would have required a land bridge connection in order to reach Sicily [70]. Our findings could also imply that AMH reached Sicily relatively late in the Upper Palaeolithic, casting further doubt on the attribution of Riparo di Fontana Nuova to the Aurignacian culture [71], a claim unsupported by absolute dating and disputed on typological grounds [8], [28]. The scenario we propose is a working hypothesis, given that only further palaeogenetic studies can confirm whether HV haplogroups are representative of those of the first AMH that migrated to Sicily.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…This complex dates to around the Last Glacial Maximum and includes species such as Equus hydruntinus (European ass) that would have required a land bridge connection in order to reach Sicily [70]. Our findings could also imply that AMH reached Sicily relatively late in the Upper Palaeolithic, casting further doubt on the attribution of Riparo di Fontana Nuova to the Aurignacian culture [71], a claim unsupported by absolute dating and disputed on typological grounds [8], [28]. The scenario we propose is a working hypothesis, given that only further palaeogenetic studies can confirm whether HV haplogroups are representative of those of the first AMH that migrated to Sicily.…”
Section: Discussionmentioning
confidence: 67%
“…The low-level consumption of marine foods by Oriente B and C is analogous to that verified, through isotope analyses, on other late Upper Palaeolithic and Mesolithic humans from Sicily [5], [8][9] and most areas of the Mediterranean [5]–[6]. On the other hand, the slightly higher δ 13 C ratio of Oriente × is similar to those of a few individuals from El Collado (Spain), Vela Spilja – Vela Luka (Croatia) and Corsica, who acquired about a fifth or more of their protein from the sea [7], [10]–[11].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The Climente II burial thus joins a small group of directly dated LUP burials from the Bølling-Allerød Interstadial (cf. Craig et al 2010;Pettitt 2010;Mannino et al 2011) and is currently the only such burial from Southeast Europe. The C-and N-isotope results add to the growing evidence that inland aquatic foods were important in the diets of some European Upper Palaeolithic groups (cf.…”
Section: Resultsmentioning
confidence: 99%
“…However, for Mesolithic sites on the Atlantic coast, including Portugal and Spain, isotope studies have shown that seafood was a major part of the diet (e.g., Richards & Hedges 1999). In contrast, an early study using both stable isotope and elemental analysis on Mesolithic coastal sites of Arene Candide in Liguria and Grotta dell'Uzzo in Sicily (Francalacci 1989;Mannino et al 2011) (Tafuri et al 2009) and Iron Age at sites in Greece and Slovenia (Murray & Schoeninger 1988). …”
Section: The Mediterranean Regionmentioning
confidence: 99%